Cytotoxicity of filtering respiratory protective devices from the waste sorting industry: a comparative study between interior layer and exhalation valve - Viegas, Carla (2021)
Filtering respiratory protection devices (FRPD) is mandatory for workers to wear in the Portuguese waste-sorting industry. Previous results regarding microbial contamination found on the FRPD interior layer raised the question of whether microbial contamination from the exhalation valve would also have cytotoxicity effects. Since the FRPD exhalation valves are very close to workers’ nose and mouth, they represent a source of exposure to bioburden by inhalation. This study aimed to evaluate the cytotoxicity of the microbial contamination present in the FRPD exhalation valves. For this purpose, the cytotoxicity effects were determined through the MTT assay in two different cell lines (human A549 epithelial lung cells, and swine kidney cells) and compared with previous results obtained with FRPD interior layers. The contamination present in the FRPD exhalation valves presented some cytotoxicity on epithelial lung cells, suggesting the inhalation route as a potential route of exposure through the use of FRPD in the waste-sorting industry. Half-maximal (50%) inhibitory concentration (IC50) values were lower for the FRPD interior layer than exhalation valves in lung cells, with overall cytotoxicity lower in exhalation valves when compared to the interior layer (z = −4.455, p = 0.000). Higher bacterial counts in TSA were correlated with lower IC50 values, thus, higher cytotoxicity effect in lung cells. No statistically significant differences were detected among different workplaces.